Jahrbuch der berufs- und wirtschaftspädagogischen Forschung 2014 - Seifried, Jürgen; Faßhauer, Uwe; Seeber, Susan (Schriftenreihe der Sektion Berufs- und Wirtschaftspädagogik der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE), 2014)
The German-speaking research on vocational education and training has always spanned a broad field, ranging from historically accentuated questions to questions of didactics and methodology, vocational teaching and learning, competence modelling and competence measurement, to university didactics and continuing vocational training. In addition, a wide range of research activities can be identified in the field of teacher training. Vocational and business education thus makes well-founded and theory-based contributions in a variety of ways to questions of vocational education and training, which are made accessible to an interested public with the current Yearbook of Vocational and Business Education Research.